A 19-year-old Patient with Recurrent Pruritus and Jaundice - K. S. Nezhdanov; E. N. Shirokova; Yu. O. Shulpekova; A. S. Ostrovskaya; M. S. Zharkova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to highlight the importance of broad differential diagnosis and possibility of conversion of benign recurrent intrahepatic cholestasis type 2 into more aggressive clinical phenotype.Key points. A 19-year-old female patient was admitted to the Clinic with skin pruritus, jaundice, dark urine, clay-colored stool, and general fatigue. Past medical history was significant for recurrent aforementioned symptoms since 3 years old, that relapsed every 1–2 years and were usually ameliorated with conservative therapy. During recent years, frequency of relapses and recovery period increased, at the same time effectiveness of medical therapy decreased. Blood chemistry results revealed an elevation of total bilirubin (up to 634 μmol/L), direct bilirubin (up to 354 μmol/L), bile acids (up to 510 μmol/L) and normal gamma glutamyl transferase level. Workup was negative for viral hepatitis, autoimmune liver diseases, obstructive choledochal lesions, storage diseases, although mutation in gene ABCB11 was found. Benign recurrent intrahepatic cholestasis type 2 was diagnosed. Following conservative therapy and plasmapheresis, jaundice and skin pruritus significantly diminished, levels of bilirubin and bile acids normalized. Regular follow up, liver biopsy and measures for relapse prevention given clinical features of aggressive phenotype were recommended.Conclusion. Identification of etiology of cholestatic liver diseases requires broad differential diagnosis. Clinical course of patients with benign recurrent intrahepatic cholestasis may transform into aggressive phenotype, reminiscent of progressive familial intrahepatic cholestasis.